2021
DOI: 10.1093/hmg/ddab201
|View full text |Cite|
|
Sign up to set email alerts
|

MiR-592 activates the mTOR kinase, ERK1/ERK2 kinase signaling and imparts neuronal differentiation signature characteristic of Group 4 medulloblastoma

Abstract: Medulloblastoma, a common malignant brain tumor in children, consists of four molecular subgroups WNT, SHH, Group 3 and Group 4. Group 3, Group 4 tumors have an overlap in their expression profiles and genetic alterations but differ significantly in their clinical characteristics, with Group 3 having the worst five-year overall survival of less than 60%. MiR-592 is overexpressed predominantly in Group 4 tumors. MiR-592 expression reduced the anchorage-independent growth, invasion potential, and tumorigenicity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…In addition to the contribution of genetic and epigenetic activation of The PI3K/Akt/mTOR pathway in medulloblastoma progression, aberrant constitutive activation of several growth factor receptors acting upstream of the PI3K/Akt/mTOR pathway has also been linked with the development and progression of some of the medulloblastoma subgroups. For instance, medulloblastoma group 4, which is considered the largest and the most diverse group, harbors multiple molecular alterations that constitutively activate several growth factor receptors, including the insulin-like growth factor (IGF), platelet-derived growth factor (PDGF), epidermal endothelial growth factor (EGFR) and vascular endothelial growth factor (VEGF) among others [ 26 , 27 , 28 ]. It has been suggested that targeting cell membrane receptors that are highly expressed on medulloblastoma cells could be one of the effective therapeutic approaches to medulloblastoma treatment.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the contribution of genetic and epigenetic activation of The PI3K/Akt/mTOR pathway in medulloblastoma progression, aberrant constitutive activation of several growth factor receptors acting upstream of the PI3K/Akt/mTOR pathway has also been linked with the development and progression of some of the medulloblastoma subgroups. For instance, medulloblastoma group 4, which is considered the largest and the most diverse group, harbors multiple molecular alterations that constitutively activate several growth factor receptors, including the insulin-like growth factor (IGF), platelet-derived growth factor (PDGF), epidermal endothelial growth factor (EGFR) and vascular endothelial growth factor (VEGF) among others [ 26 , 27 , 28 ]. It has been suggested that targeting cell membrane receptors that are highly expressed on medulloblastoma cells could be one of the effective therapeutic approaches to medulloblastoma treatment.…”
Section: Resultsmentioning
confidence: 99%
“…MiR-592 suppresses the malignant phenotypes of thyroid cancer through the regulation of lncRNA NEAT1 and downregulation of NOVA1 [ 34 ]. A miR-592-mediated activation of mTOR (mammalian target of rapamycin), ERK1/ERK2 signaling, and neuronal differentiation impart group 4 medulloblastoma characteristics [ 35 ]. It has been found that lncRNA MEF2C-AS1 inhibits cervical cancer by targeting RSPO1 by suppressing miR-592 [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Wnt signaling and WISP1 are vital pathways during metabolic disorders and DM for the oversight of oxidative stress, programmed cell death, and non-coding RNA function (Figure 2). Wnt proteins, which are cysteine-rich glycosylated proteins, are part of the wingless pathway that can modulate cell development and survival during aging, cardiovascular disorders, tumorigenesis, organogenesis, neurodegeneration, vascular disease, inflammation, and DM [25,28,48,76,92,115,131,150,184,276,296,297,305,307,338,339,[457][458][459][460][461][462][463][464][465][466][467]. Wnt proteins that can involve Wnt1 oversee programmed cell death [105,219,278,299,339,362,387,[467][468][469][470][471][472], pancreatic β-cell development and growth [473], skeletal function [152,305,307], trophic factor protec...…”
Section: Wnt Signaling and Wisp1 Oversight In Diabetes Mellitus And M...mentioning
confidence: 99%